The privilege of knowing better: Female millennial demographics and the representation of homophobia on teen TV. (1st June 2018) - Peters, Wendy
The 2010–11 seasons of 90210 (2008–13), Degrassi (2010–15), Glee (2009–15) and Pretty Little Liars (2010–17) represent homophobia as arising from closeted teens, cisgender male 'jocks', racialized characters and immigrants. Rather than locating homophobia and heteronormativity within the social fabric and minds of all who have been steeped in American and Canadian hegemonic beliefs, homophobic characters are framed as rare, anachronistic and out-of-step with the seemingly post-homophobia ethos they exist within. Drawing on media trade publications, I place these patterns for representing homophobia in their market context, arguing that profit motives encourage representations of gay teens and homophobia that suggest homophobic beliefs are the domain of 'others', apart from the privileged viewer of teen TV: affluent, educated, female, white and non-white millennials aged 18–34. The target viewers are invited to see themselves as innocent and enlightened in relation to homophobic others, while prescribing a cure to homophobia that emphasizes individual change over social change.